THE SIGNIFICANCE OF ISLAMIC EDUCATION INTEGRATION IN SUSTAINABLE DEVELOPMENT GOALS IN PURWOKERTO - Asdlori Asdlori; Muhamad Slamet Yahya (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2023)
This study aims to investigate the integration of Islamic education and Sustainable Development Goals (SDGs) in Purwokerto. The background highlights the significance of Islamic education in promoting values aligned with the SDGs, while also addressing the challenges of conservative interpretations and the need for inclusive approaches. The research aims to analyze the role of the Faculty of Education and Teacher Training in implementing SDGs through its curriculum, research activities, and community engagement. The findings reveal that the integration of Islamic education and SDGs in Purwokerto can foster a comprehensive approach to sustainable development, promoting environmental stewardship, social justice, and economic equity. The discussion emphasizes the importance of inclusive interpretations, curriculum development, and partnerships with various stakeholders. In conclusion, the study emphasizes the potential of Islamic education as a transformative force in achieving the SDGs in Purwokerto, while calling for ongoing efforts to address challenges and maximize the positive impact of integration.